Determinants of LPD Performance: Collaboration of Stewardship, Organizational Culture, and Leadership Theory Based on Arthasastra - Ni Putu Ayu Kusumawati; Ni Made Wisni Arie Pramuki; Putu Cita Ayu (Jurnal Ilmiah Akuntansi, 2024)
This research aims to examine the influence of good corporate governance (GCG) with Tri Hita Karana (THK) organizational culture and Sad Warnaning Rajaniti's leadership as moderators on the performance of Village Credit Institutions (LPD) in Bali. The study population comprises LPD heads throughout Bali, with a sample size of 315 respondents selected using stratified random sampling. Data were collected and analyzed using the SEM-PLS method to test the hypotheses. The results indicate that LPD performance can be significantly enhanced through improvements in governance, which includes both Sekala (tangible) and Niskala (intangible) aspects of GCG. Additionally, the THK culture, encompassing Parahyangan (spiritual harmony), Pawongan (social harmony), and Palemahan (environmental harmony), along with the implementation of Sad Warnaning Rajaniti leadership, positively influences LPD performance. Furthermore, the study finds that THK culture and Sad Warnaning Rajaniti leadership act as effective moderators in this relationship. These findings have important implications for the development of accounting literature by integrating management aspects, such as GCG implementation, leadership based on Sad Warnaning Rajaniti, and THK organizational culture, to improve LPD performance. This research contributes valuable insights for policymakers and practitioners in enhancing the governance and leadership frameworks of LPDs in Bali.